Meningkatkan Proses Dan Hasil Belajar IPAS Menggunakan Model Discovery Learning Pada Siswa Kelas V SD N 081/VIII Wanareja - Agnes Amelia; Megawati; Opi Andriani (Jurnal Tunas Pendidikan, 2025)
This research is motivated by the lack of maximizing the IPAS learning process, so that it has an impact on the learning outcomes of IPAS students in class V SD N 081 / VIII Wanareja. This study aims to improve the process and learning outcomes of students using the discovery learning model in IPAS subjects in class V SD N 081/VIII Wanareja. The research method used is Classroom Action Research (PTK). The subjects of this study were fifth grade students of SD N 081/VIII Wanareja consisting of 22 students each consisting of 13 boys and 9 girls. This research was conducted in class V of SD N 081/VIII Wanareja which was carried out in two cycles. The data collection techniques used were observation, tests, and documentation. The research instruments used were teacher observation sheets, student observation sheets, and learning outcomes test questions. The data analysis techniques used are quantitative data and qualitative data. Based on the results of this study, the student learning process in cycle I was 52,3% and in cycle II it increased to 88,9%, while the learning process observed by homeroom teacher V was in cycle I 83,8% and in cycle II it increased to 96,7%. The learning outcomes of students who achieved KKTP in cycle I were 54,5% and in cycle II increased to 81,8%. It can be concluded that by applying the discovery learning model can improve the process and learning outcomes of students in IPAS subjects in class V SD N 081/VIII Wanareja.